Research of Key Technology for Macroscopic Hydrogen Induced Injury Testing and In-Service Monitoring of Pressure Vessel in Wet Hydrogen Sulfide Environment. (2015) - Chen, D.Y.; Wang, D.; Chen, H.; Yang, Q.; Xiang, Y.X.
Abstract: The hydrogen induced injury detection and propagation monitoring of pressure vessels serviced in wet hydrogen sulfide environment is one of problems needs to be solved urgently for petrochemical device long-term operation. According to the key technology and difficulties of macroscopic hydrogen induced injury testing and in-service monitoring of pressure vessels in wet hydrogen sulfide environment, multiple ultrasonic nondestructive testing technologies were used. In order to realize rapid detection for macroscopic hydrogen induced injury of large area, electromagnetic ultrasonic technologies were used to test the pressure vessel cutting board, and ultrasonic guided wave technique was used to research the HB artificial simulated test plate by simulation and testing; Ultrasonic phased array was used to measure defects accurately for pressure vessels which have hydrogen induced injury; The electromagnetic ultrasonic technology was used to study its in-service monitoring, and the expansion situation caused by macroscopic hydrogen induced injury was monitored; It were provided foundation for hydrogen induced injury diagnosis and safety evaluation after FFS evaluation by study and application of these detection techniques.